Hepatitis delta infection among persons living with HIV in Europe. (21st January 2023) - Béguelin, Charles; Atkinson, Andrew; Boyd, Anders; Falconer, Karolin; Kirkby, Nikolai; Suter‐Riniker, Franziska; Günthard, Huldrych F.; Rockstroh, Jürgen K.; Mocroft, Amanda; Rauch, Andri; Peters, Lars; Wandeler, Gilles; et al.
Abstract: Background and Aims: A high prevalence of hepatitis delta virus (HDV) infection, the most severe form of viral hepatitis, has been reported among persons living with HIV (PLWH) in Europe. We analysed data from a large HIV cohort collaboration to characterize HDV epidemiological trends across Europe, as well as its impact on clinical outcomes. Methods: All PLWH with a positive hepatitis B surface antigen (HBsAg) in the Swiss HIV Cohort Study and EuroSIDA between 1988 and 2019 were tested for anti‐HDV antibodies and, if positive, for HDV RNA. Demographic and clinical characteristics at initiation of antiretroviral therapy were compared between HDV‐positive and HDV‐negative individuals using descriptive statistics. The associations between HDV infection and overall mortality, liver‐related mortality as well as hepatocellular carcinoma (HCC) were assessed using cumulative incidence plots and cause‐specific multivariable Cox regression. Results: Of 2793 HBsAg‐positive participants, 1556 (56%) had stored serum available and were included. The prevalence of HDV coinfection was 15.2% (237/1556, 95% confidence interval [CI]: 13.5%–17.1%) and 66% (132/200) of HDV‐positive individuals had active HDV replication. Among persons who inject drugs (PWID), the prevalence of HDV coinfection was 50.5% (182/360, 95% CI: 45.3%–55.7%), with similar estimates across Europe, compared to 4.7% (52/1109, 95% CI: 3.5%–5.9%) among other participants. During a median follow‐up of 10.8 years (interquartile range 5.6–17.8), 82 (34.6%) HDV‐positive and 265 (20.1%) HDV‐negative individuals died. 41.5% (34/82) of deaths were liver‐related in HDV‐positive individuals compared to 17.7% (47/265) in HDV‐negative individuals. HDV infection was associated with overall mortality (adjusted hazard ratio 1.6; 95% CI 1.2–2.1), liver‐related death (2.9, 1.6–5.0) and HCC (6.3, 2.5–16.0). Conclusion: We found a very high prevalence of hepatitis delta among PWID across Europe. Among PLWH who do not inject drugs, the prevalence was similar to that reported from populations without HIV. HDV coinfection was associated with liver‐related mortality and HCC incidence.